2019
DOI: 10.1155/2019/4215989
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-Orbito-Cerebral Mucormycosis: Two Cases with Amaurosis as Presentation, Medical Surgical Management and Follow-Up

Abstract: Purpose: Mucormycosis is an infection caused by fungi to the class Zygomycetes that usually appears in immunosuppressed patients. Diagnostic confirmation is often delayed, with fatal prognosis in cases in which treatment is not rapidly established. Case report: We present two clinical cases of rhino-orbito-cerebral mucormycosis with an atypical presentation form, consisting of a unilateral complete sudden vision loss. Intravenous treatment with liposomal amphotericin B was started and total orbital exenteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…As reported in multiple cases, mucormycosis may affect brain vessels. In general, for central nervous system [ 36 , 37 ] involvement, imaging studies, such as CT-scans, MRI, and angiography, are recommended to rule out neurological compromise and infection, as we did for our case. Although our patient did not exhibit direct neurological affectation, he did present with a constellation of neuro-ophthalmological manifestations, including, headache, diplopia, decreased visual acuity in the right eye, and amaurosis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As reported in multiple cases, mucormycosis may affect brain vessels. In general, for central nervous system [ 36 , 37 ] involvement, imaging studies, such as CT-scans, MRI, and angiography, are recommended to rule out neurological compromise and infection, as we did for our case. Although our patient did not exhibit direct neurological affectation, he did present with a constellation of neuro-ophthalmological manifestations, including, headache, diplopia, decreased visual acuity in the right eye, and amaurosis.…”
Section: Discussionmentioning
confidence: 86%
“…This case was a 55-year-old diabetic male who complained of headache, maxillary sinus pain, and diplopia for three days, in whom mucormycosis was later confirmed [ 36 ]. Likewise, two cases were reported from Spain in 2019, both patients in their 50s, one diabetic, the other in chronic renal failure, who presented sudden unilateral amaurosis depicting an atypical presentation form of rhino-orbital-cerebral mucormycosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vironneau et al (2014) showed a statistically significant difference in mortality between patients who received topical therapy or without. Navarro-Perea et al (2019) presented a case of improvement with surgery combined with local therapy and emphasized the importance of topical management. Joos and Patel (2017) also proposed conservative orbital debridement with local antifungal irrigation is a viable option as well.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs predominantly in immunocompromised individuals or patients with co-morbid conditions though cases are also reported in healthy individuals. [ 1 2 ] The risk factors attributing to the development of mucormycosis are diabetes mellitus (especially uncontrolled diabetes like diabetic ketoacidosis), solid organ transplantation, neutropenia, long-term systemic corticosteroid use, and any other etiology causing immunosuppression. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Mucormycosis can manifest in many different clinical forms, including rhino-orbito-cerebral (ROC), pulmonary, cutaneous, gastrointestinal, disseminated, and other unusual presentations. [ 1 ] Out of these rhino-orbital-cerebral-mucormycosis (ROCM) is the most common form of mucormycosis which occurs as a result of inhalation of the fungal spores by the host leading to rapidly progressive disease. It disseminates from the sino-nasal tissues to the involvement of orbits and finally the central nervous system.…”
Section: Introductionmentioning
confidence: 99%